Theistic Evolutionists’ View of the Words Bashar and Insan in the Qur’an: A Critical Analysis - Elshahat, Ibrahim; Ahmadi Ramchahi, Abdullatif; Mohd Yusoff, Mohd Yakub @ Zulkifli (Afkar: Jurnal Akidah dan Pemikiran Islam, 2019)
This research is a qualitative study that examines the theistic evolutionists’ view, interpretations, and translations of the words bashar and insan in the Qur’an through a comparative and analytical analysis. Some theistic evolutionists understood the word bashar to refer to hominids, and the word insan to refer to Homosapiens. Alternatively, other theistic evolutionists understood the word bashar to refer to Homosapiens, and the word insan to refer to hominids. This study sheds light on the grounds of this contradiction and concludes that attempts to interpret the Quranic account of human beings and Adam from an evolutionary perspective are incorrect. On the other hand, the study concludes that the words bashar and insan are synonymous terms. The article proposes that the correct understanding and authentic interpretation of the terms are ‘human beings.’